Conformation of beef and dairy cattle - Snodgrass, Milton David (My University, 1906)
Introduction: The conformation of an animal means not only the outward form, the manner in which the body is formed, the particular structure, texture, and the disposition of the parts which compose it; but, also its adaptation to some purpose or effect. Function and conformation are so closely related that one is often surprised to find excellencies in one direction when the other is nearly or wholly lacking. One sometimes finds excellent conformation of parts in an animal with impaired function of certain parts, while occasionally the reverse is true. Generally speaking, the two are associated together. As a rule to guide us, one must accept them as being closely related. By some people they are held to be independent of each other; some hold, that conformation is the measure of utility, while others place their faith upon function alone. In treating this subject it is the writers desire to place before his readers in as concise form as possible some of the fundamental features underlying successful management, breeding, and feeding of beef and dairy cattle. Men usually keep what they consider the best type of cattle for their particular purpose. By a glance over this or that herd one can determine very closely the owner's idea of a good beef or dairy animal. When one finds in a dairy herd of the feeding pen every imaginable type of animal, he knows there is a lack of knowledge upon the stockman's part of what constitutes a good beef or dairy animal. This lack of uniformity of type exists in nearly every herd we see among the farmers of today. We naturally conclude that the average man who handles stock has a very limited knowledge of the possibilities of his herd. He does not stop to think that the profit on a few of his best cows or steers is wholly or nearly eaten up by the poor milkers or feeders.
Citation: Snodgrass, Milton David. Conformation of beef and dairy cattle. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Animal Science; Conformation; Beef Cattle; Dairy Cattle; Theses